Village Aplication Perfomance Evaluation: Analysis of The Smart Kampung Application in Ketapang, Banyuwangi - Putra, I Made Arie Widyasthana Wartana; Dinata, Chandra; Poespitohadi, Wibisono; Putri Nadila, Albareta Aulia (PUBLIC CORNER, 2024)
This article aims to highlight the performance of the Smart Kampung application and website in Ketapang Village, Banyuwangi Regency, as well as to understand the extent to which digital technology can improve the efficiency of public services and empower village communities. This evaluation of the Smart Kampung web application uses a qualitative content analysis approach, which involves collecting and analyzing textual and visual data from the Smart Kampung platform. Data sources include descriptive text, usage guides, user reviews, and visual content such as images and video tutorials. The findings in this article are that the Smart Village program has succeeded in integrating various public services into one digital platform that residents can access easily. This platform facilitates access to population administration, health, and education services and empowers the local economy through online marketing training and developing MSMEs. Analysis of user feedback shows that although the community generally receives the platform well, several areas still require improvement to increase user satisfaction. This article will help explain the use of technology at the village level and practical recommendations for optimizing the previous Smart Village platform. Apart from that, these findings can also guide other villages that want to adopt similar programs so that the benefits of digital technology can be felt more widely throughout rural areas in Indonesia. Keywords: Application, Digital Village, Evaluation, Smart Kampung